Rancang Bagun Sistem Informasi Penentuan Rute Terbaik Menggunakan Algoritma Ant Colony Optimization dan Fuzzy-AHP - hidayat, erzi; Perdana Sari, Rika; Dewi, Meilany; Hakim, Arif Rahman (Politeknik Caltex Riau, 2024)
The determination of tourist routes in Pekanbaru is not solely based on identifying the shortest route but also the best route, considering the various challenges in the field, such as potholes, traffic congestion, and the lack of directional signs to tourist destinations. The selection of the best route is crucial to improving travel comfort and efficiency, reducing travel time, and avoiding potential risks that may disrupt the tourist experience. Therefore, this study aims to determine the best route to tourist attractions using the Ant Colony Optimization (ACO) method and rank tourist routes with the Analytic Hierarchy Process (AHP) method. This study integrates two approaches: ACO, which mimics the behavior of ant colonies in finding optimal routes, and AHP, which generates numerical scores to rank alternatives based on how well each alternative meets the decision maker's criteria. The results of this study are expected to help tourists find available facilities at tourist attractions and provide alternative routes that can serve as a reference in determining the best route to the tourist location, thereby enhancing tourist satisfaction and the overall travel experience.